2014
DOI: 10.1246/cl.140261
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Carbon Dioxide Reduction Catalyzed by a Dinuclear Ruthenium Complex with a Flexible Bridging Ligand

Abstract: A dinuclear Ru complex, [{Ru(tpy)Cl} 2 (¯-L)](PF 6 ) 2 (1), was synthesized by the reaction of the flexible bridging ligand L (= N,N¤-bis(5-bipyridylhexyl)-cis-1,4-cyclohexanediamine) with [Ru(tpy)Cl 3 ]. The complex contained two [Ru(tpy)(bpy)Cl] + moieties linked by L, and the reaction of 1 with AgNO 3 allowed for isolation of the ligand-exchanged product [{Ru(tpy)-(Solv.)} 2 (¯-L)](PF 6 ) 4 (2). The behavior of 2 as a CO 2 reduction electrocatalyst was investigated in acetonitrile. Under N 2 , two reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…1,2 The mixed-valence binuclear (or hybrid) complex has been widely used to speed up CO 2 reduction. [3][4][5] The previous study by Kuramochi et al reported that an electrochemical ruthenium (Ru) catalyst to yield the CO as well as rhenium (Re) complex also has been extensively used. 4 Suntharalingam et al studied the homogeneous metal complex and investigated mono-and bimetallic terpyridine complexes in DNA binding.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The mixed-valence binuclear (or hybrid) complex has been widely used to speed up CO 2 reduction. [3][4][5] The previous study by Kuramochi et al reported that an electrochemical ruthenium (Ru) catalyst to yield the CO as well as rhenium (Re) complex also has been extensively used. 4 Suntharalingam et al studied the homogeneous metal complex and investigated mono-and bimetallic terpyridine complexes in DNA binding.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The previous study by Kuramochi et al reported that an electrochemical ruthenium (Ru) catalyst to yield the CO as well as rhenium (Re) complex also has been extensively used. 4 Suntharalingam et al studied the homogeneous metal complex and investigated mono-and bimetallic terpyridine complexes in DNA binding. 6 They found that using two transition metals is better than one metal because of its strong corresponding to the photoexcitation properties.…”
Section: Introductionmentioning
confidence: 99%